Synthesis and characterization of porous forsterite (Mg2SiO4)-filled polystyrene composites - Dong, Xue; Asghar, Ghulam; Yoo, Chan Sei; Woo, Chaeheon; Jeon, Jiho; Kang, Jinsu; Zhang, Xiaojie; Bang, Hyeonseok; Kim, Yoengjin; Oh, Hyung Suk; Yu, Hak Ki; Choi, Jae Young (Journal of Materials Science, 2023)
With the increasing demand for wireless communication technology in the microwave frequency range, the development of composite materials with low dielectric constant and low loss is essential. In this study, we synthesized core–shell structured porous MgO microspheres with SiO2 layers, which were subsequently calcinated at 800 °C to obtain a pure Mg2SiO4 phase. The pure Mg2SiO4 filler was then incorporated into polystyrene (PS) to make composites with varying filler volume percentages. The morphology and phase transformation of the synthesized samples were analyzed using scanning electron microscopy and X-ray diffraction, respectively. The dielectric properties of the PS-Mg2SiO4 composites were investigated at 9.4 GHz. The obtained results indicate that the dielectric constant and dielectric loss of the composite increase with filler volume percentage. The PS-Mg2SiO4 composite with 30 vol% filler demonstrated the most promising dielectric properties, with a dielectric constant of 2.79 and a dielectric loss of 0.0085 at 9.4 GHz. These findings confirm that the PS-Mg2SiO4 composite has potential applications in faster and more secure wireless communication technology in the microwave frequency range.
Keywords: Composites material; Dielectrics property; Forsterites; Low dielectric constants; Microwave frequency ranges; Polystyrene composites; Synthesis and characterizations; Synthesised; Volume percentage; Wireless communication technology